2022
DOI: 10.2147/jir.s355881
|View full text |Cite
|
Sign up to set email alerts
|

Novel Th17 Lymphocyte Populations, Th17.1 and PD1+Th17, are Increased in Takayasu Arteritis, and Both Th17 and Th17.1 Sub-Populations Associate with Active Disease

Abstract: Purpose We evaluated T helper lymphocyte profile, including novel Th17 subsets Th17.1 (secrete IFN-γ, associate with corticosteroid resistance) and PD1+Th17 (secrete TGF-β1, implicated in fibrosis), and related cytokines in peripheral blood of Takayasu arteritis (TAK). Materials and Methods We evaluated circulating Th1, Th2, Th17, Th17.1, PD1+CD4+ T lymphocytes, PD1+Th17, and Treg lymphocytes, inflammatory (IFN-γ, IL-4, IL-6, IL-17A, IL-23, IL-1β, TNF-α) and regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 57 publications
(66 reference statements)
1
25
0
Order By: Relevance
“…Recently, an increase in Th17.1 cells producing both IL-17 and IFNγ was observed in TAK patients compared with healthy controls. Similar results were described for PD1 + Th17 cells ( 72 ). Finally, IL-17A and Th17-related cytokines trigger neutrophil recruitment and activation that could contribute to vascular lesions ( 73 ).…”
Section: Role Of the Th17 Pathway In Vasculitissupporting
confidence: 87%
“…Recently, an increase in Th17.1 cells producing both IL-17 and IFNγ was observed in TAK patients compared with healthy controls. Similar results were described for PD1 + Th17 cells ( 72 ). Finally, IL-17A and Th17-related cytokines trigger neutrophil recruitment and activation that could contribute to vascular lesions ( 73 ).…”
Section: Role Of the Th17 Pathway In Vasculitissupporting
confidence: 87%
“…A recent study comparing 30 patients with active TAK with 27 patients with inactive TAK reported increased Th17 and Th17.1 lymphocytes in active TAK on univariable analyses. However, Th17 lymphocytes (but not Th17.1 lymphocytes) remained associated with active TAK after adjustment for CRP and Th1, Th2, and T regulatory lymphocyte populations [ 109 ]. Another study analyzed gene expression on peripheral blood mononuclear cells in eleven patients with active TAK compared with nine with inactive TAK (disease activity assessed using the NIH criteria).…”
Section: Circulating Biomarkers Of Disease Activity In Takmentioning
confidence: 99%
“…A further study compared serum cytokines in 29 TAK with active disease with 27 with inactive disease. The levels of inflammatory or regulatory cytokines were not significantly different between these two groups [ 109 ]. Another study compared various inflammatory and regulatory cytokines (including IL-6) between 15 TAK with the active disease and 17 with inactive disease.…”
Section: Circulating Biomarkers Of Disease Activity In Takmentioning
confidence: 99%
“…Unveiling the contribution of Th17.1 cells to induce and sustain inflammatory responses has been a significant breakthrough to decipher autoimmune processes far beyond the neuroinflammation field. [63][64][65] 2.1.4 | Th5/ThGM-CSF: making space for newcomers…”
Section: Cd4 T Cellsmentioning
confidence: 99%
“…Although GM‐CSF production is not exclusive to the ex‐Th17 subset, the high activity and trafficking of these cells, as well as their co‐production of potent inflammatory cytokines make them key promoters of neuroinflammation. Unveiling the contribution of Th17.1 cells to induce and sustain inflammatory responses has been a significant breakthrough to decipher autoimmune processes far beyond the neuroinflammation field 63‐65 …”
Section: Inflammatory T Cells In Msmentioning
confidence: 99%